Political money crimes from the perspective of positive law and Islamic criminal law - Muhamad Rafik Hidayat; Muhamad Kholid; Enceng Arif Faizal (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
The practice of vote-buying has been prohibited by law, but it remains a problem in the conduct of elections in Indonesia. Normatively, vote-buying is classified as a criminal offense, yet its persistence highlights a tension between the ideal of electoral justice and transactional political practices. This study aims to analyze the regulation of money politics as a criminal offense in Law No. 10 of 2016 and to examine its normative relevance to the concept of risywah as well as ta‘zīr sanctions in Islamic criminal law. This study employs a normative legal approach using descriptive-analytical and qualitative research methods, incorporating legislative, conceptual, and comparative legal approaches through an examination of legislation, legal doctrine, and fiqh al-jinayah literature. The research findings indicate that money politics substantially shares similar characteristics with bribery, as both involve the provision of material benefits to unlawfully influence choices or decisions. Furthermore, the sanction provisions in Law No. 10 of 2016, which grant judges discretion through minimum and maximum sentencing limits, demonstrate conceptual alignment with ta‘zīr in Islamic criminal law. This normative alignment confirms that both positive law and Islamic criminal law regard vote-buying as a prohibited act because it contradicts justice, the public interest, and the integrity of the democratic process.